Gambaran Strategi Koping Wanita dengan Peran Ganda dalam Menghadapi Stereotip Sosial dan Kesejahteraan Psikologis yang Rendah - Purnamawati, Agustin Mega (CV. SINAR HOWUHOWU, 2025)
This article examines the description of coping strategies used in dealing with social stereotypes and low psychological well-being in women with dual roles as housewives who already have children as well as honorary teachers in Padangan village, Tulungagung, East Java. This study aims to analyze the extent to which coping strategies are described based on the dimensions of psychological well-being and to analyze the extent to which factors play a role in determining appropriate coping strategies for women with multiple roles. Ecological development theory (ecological system theory) Urie Bronfenbrenner which emphasizes the role of the environment in the formation of human development and a multidimensional approach by Carol D. Ryff and Corey Lee M. Keyes psychological well-being theory is used to understand the factors that play a role in determine coping strategies by analyzing how positive changes women with multiple roles are facing based on the environment that influences them. This study used a qualitative method with data collection techniques in the form of in-depth interviews with women with dual roles as honorary teachers who have 8 children as informants. Through this research, the authors found that women with multiple roles in Padangan village had various coping strategies, including problem focused coping strategies: instrumental social support from husbands and parents, and actively looking for opportunities to prove their abilities, while emotion focused coping strategies: inspiration from other people. others, good time management, worship, prayer, reading the Koran, attending recitations, listening to motivation, and getting help from a partner. Meanwhile, the factors that play a role in determining coping strategies are various conflicts: negative social stigma, poor time management, heavy workload, need for strong x support and financial problems. In addition, the stereotypes that arise from the environment of the ecosystem, microsystem, macrosystem, and chronosystem in women with multiple roles greatly determine the psychological well-being and coping strategies chosen. Keywords: Psychological well-being, social stereotypes, coping strategies, multiple roles.